2005
DOI: 10.1007/s10554-005-9029-8
|View full text |Cite
|
Sign up to set email alerts
|

Novel diagnostic catheter specifically designed for both coronary arteries via the right transradial approach

Abstract: The aim of this study was to assess the feasibility, safety, and performance of a novel diagnostic catheter specifically designed for engaging both coronary arteries via the right transradial artery approach. A total of 160 patients were randomized between the standard Judkins (5F R4, L4; Cordis Corporation, Miami, FL) and the 5F Tiger II (Terumo Corporation, Tokyo, Japan) catheters. End points included the duration of various procedures and the assessments of angiographic image quality and catheter performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
43
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 15 publications
6
43
1
Order By: Relevance
“…We previously found that a single 5F multipurpose catheter via the TRA had no effect on the coronary angiography success rate (8), a finding confirmed in the present study on peripheral artery angiography. Although treatment with nitroglycerin (100 µg) and lidocaine (200 µg) could reduce the incidence of radial artery spasm (20,21), use of a single multipurpose catheter may also avoid radial artery spasm (8,22). Since the path from the right radial to the renal artery is long and extends across the aortic arch, the length of a multipurpose catheter is sometimes insufficient (8,23).…”
Section: Discussionmentioning
confidence: 99%
“…We previously found that a single 5F multipurpose catheter via the TRA had no effect on the coronary angiography success rate (8), a finding confirmed in the present study on peripheral artery angiography. Although treatment with nitroglycerin (100 µg) and lidocaine (200 µg) could reduce the incidence of radial artery spasm (20,21), use of a single multipurpose catheter may also avoid radial artery spasm (8,22). Since the path from the right radial to the renal artery is long and extends across the aortic arch, the length of a multipurpose catheter is sometimes insufficient (8,23).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a long tipped catheter is used for left coronary artery and a short tipped catheter is used for right coronary artery. 11 In case of anomalous RCA with high anterior takeoff short tipped right catheters don't reach the ostium and left catheters don't provide adequate back-up, as they tend to maintain their original configuration to the right side of ascending aorta. However, TIG catheter due to its versatile design rests against the posterior wall of ascending aorta and long tip easily reaches the ostium.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, many attempts have been made to design a catheter for a transradial approach for routine diagnostic and interventional coronary procedures, trying to engage both coronary arteries by one single catheter [3]. For example, the 5F Tiger II (Terumo Corporation, Tokyo, Japan) catheters were tested to prove the feasibility, safety, and performance as a kind of multipurpose catheter for transradial coronary angiography [4]. The Brachial Type K (Terumo Outlook, Leuven, Belgium) catheters were also proved to to perform both left and right coronary angiography with a single catheter [5].…”
Section: Discussionmentioning
confidence: 99%